Trends in body size and prevalence of underweight and overweight in 7–9 year old children from eastern Poland between 2006 and 2021 - Wasiluk, Agnieszka; Bodasińska, Anna; Saczuk, Jerzy (Anthropological Review, 2023)
Malnutrition and the overnutrition of children and adolescents is a severe problem in most countries. Aim of the study: Determination of fifteen-year changes in body height, and BMI in girls and boys living in towns and villages in eastern Polish voivodeships.In 2006, 2016, and 2021 a study was conducted on children and adolescents living in the Podlaskie, Lubelskie, and Podkarpackie voivodeships (7048 girls and 7686 boys aged 7–9 years). Body mass index (BMI) was calculated based on height and weight measurements. In the calendar age groups, arithmetic means and dissemination measures for body height and BMI were calculated on particular time periods of the study. The statistical significance of the differences between the groups was conducted using the ANOVA analysis of variance and the Newmann-Keuls test. From the research material, study participants exhibiting underweight, overweight and those falling within a normal range of weight-to-height proportions were selected taking into account places of residence (town, village). The statistical significance of the differences between the number of people classified into the above-described groups was determined using the χ² test.In the analysed period in groups of girls, a systematic increase in body height was observed. However, in boys, such tendency was found only in rural residents. In the period of 2006–2016, greater changes in BMI were found in girls from rural areas and boys from cities. The opposite observation was recorded in the 2016–2021 period. In the years between 2006 and 2021, the incidence of both underweight and normal BMI decreased, while the incidence of overweight and obesity increased.Our results indicate the need for conducting systematic research assessing the nutritional status of young people living in the Lubelskie and Podlaskie voivodships, as well as an in-depth analysis of the causes of malnutrition and undertaking educational activities.